2022
DOI: 10.1080/21645515.2022.2153538
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of public health measures and vaccine acceptance during the COVID-19 pandemic in rural Zambia

Abstract: Vaccines are effective tools to prevent COVID-19-related morbidity. However, coverage is low throughout sub-Saharan Africa. Uptake of public health measures, perceptions of COVID-19 illness and vaccines, and intention to vaccinate were evaluated in 2021–2022 in rural Zambia. Adherence to public health measures, perceptions of COVID-19 risk and severity, and vaccine acceptance increased significantly over time, particularly in December 2021, coinciding with the fourth pandemic wave and relaunch of the national … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…However, a multivariate logistic regression of factors associated with people getting vaccinated against COVID-19 indicated that number of people in the household, smoking cigarettes, drinking alcohol and heard of COVID-19 were not associated with people getting vaccinated against COVID-19. These findings are similar to another study by Sutcliffe et al (2022), which found that COVID-19 vaccines hesitancy in Africa was attributed to lack of confidence or knowledge of the vaccines, religious beliefs, lack of perceived risks of COVID-19 and mistrust of public health institutions [5,14].…”
Section: /9supporting
confidence: 90%
See 2 more Smart Citations
“…However, a multivariate logistic regression of factors associated with people getting vaccinated against COVID-19 indicated that number of people in the household, smoking cigarettes, drinking alcohol and heard of COVID-19 were not associated with people getting vaccinated against COVID-19. These findings are similar to another study by Sutcliffe et al (2022), which found that COVID-19 vaccines hesitancy in Africa was attributed to lack of confidence or knowledge of the vaccines, religious beliefs, lack of perceived risks of COVID-19 and mistrust of public health institutions [5,14].…”
Section: /9supporting
confidence: 90%
“…Scaling up and implementation of COVID-19 vaccination programs have received much attention in most low and middle-income countries like Zambia. The Republic of Zambia, through the Ministry of Health, officially launched its COVID-19 vaccination campaign on 14 April 2021, after receiving the first consignment of 228,000 doses of the vaccines from the COVAX facility, a global initiative representing a partnership among the World Health Organization, the Global Alliance for Vaccines and Immunization, UNICEF and the Coalition for Epidemic Preparedness Innovations, working on the equitable distribution of COVID-19 vaccines [5]. Despite the huge efforts made towards achieving a successful COVID-19 vaccination campaign in Zambia, the country remained with the lowest vaccination rate among the eligible population with only 25,644 individuals fully vaccinated as of 9 October 2022, which translated into 5.4% of the total eligible population [9].…”
Section: /9mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2021, an increase in prevalence among outpatients mid-year coincided with a peak in cases nationally [11] and introduction of the Delta SARS-CoV-2 variant into the community [13] . During this time, visits to the outpatient department decreased, potentially due to concerns about traveling or attending healthcare facilities and public health activities (e.g., contact tracing) in the community [14] . The prevalence increased again at the end of 2021, coinciding with introduction of the Omicron SARS-CoV-2 variant.…”
Section: Discussionmentioning
confidence: 99%